(3x-2y\2x^2-3xy+3x+2y\2x^2+3xy)*4x^2-9y^2\x^2-y^2

0 голосов
52 просмотров

(3x-2y\2x^2-3xy+3x+2y\2x^2+3xy)*4x^2-9y^2\x^2-y^2


Алгебра (15 баллов) | 52 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

 ((3x-2y)/(2x²-3xy)+(3x+2y)/(2x²+3xy))*((4x²-9y²)/(x²-y²))=
Упростим первый множитель:
(3x-2x)/(x(2x-3y)+(3x+2y)/(x(2x+3y))=
=((3x-2y)(2x+3y)+(3x+2y)(2x-3y))/(x(4x²-9y²))=
=(6x²+9xy-4xy-6y²+6x²+4xy-9xy-6y²)/(x(4x²-9y²))=
=(12x²-12y²)/(x(4x²-9y²))=12(x²-y²)/(x(4x²-9y²))=  
12(x²-y²)(4x²-9y²)/((x(4x²-9y²)((x²-y²))=12/x.
  

(251k баллов)